2021
DOI: 10.1016/j.redox.2020.101816
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalyx sialic acids regulate Nrf2-mediated signaling by fluid shear stress in human endothelial cells

Abstract: Activation of the nuclear factor erythroid 2–related factor 2 (Nrf2) pathway is critical for vascular endothelial redox homeostasis in regions of high, unidirectional shear stress (USS), however the underlying mechanosensitive mediators are not fully understood. The endothelial glycocalyx is disrupted in arterial areas exposed to disturbed blood flow that also exhibit enhanced oxidative stress leading to atherogenesis. We investigated the contribution of glycocalyx sialic acids (SIA) to Nrf2 signaling in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 99 publications
0
29
0
Order By: Relevance
“…SDC-1 in the glycocalyx plays an important role in response to ischemia-reperfusion injury, hyperglycemia, endotoxemia, septic shock, and abnormal blood shear stress. [21][22][23][24] Chen et al also showed that pretreatment with NAH protects HS shedding from the intestinal mucosal surfaces in cecal ligation and perforation-induced mouse septic intestinal injury. 25 The results in the present study showed that downregulation of MMP-9 is significantly protected against LPS-induced SDC-1 shedding, thereby reducing the damage to tight junction.…”
Section: Discussionmentioning
confidence: 98%
“…SDC-1 in the glycocalyx plays an important role in response to ischemia-reperfusion injury, hyperglycemia, endotoxemia, septic shock, and abnormal blood shear stress. [21][22][23][24] Chen et al also showed that pretreatment with NAH protects HS shedding from the intestinal mucosal surfaces in cecal ligation and perforation-induced mouse septic intestinal injury. 25 The results in the present study showed that downregulation of MMP-9 is significantly protected against LPS-induced SDC-1 shedding, thereby reducing the damage to tight junction.…”
Section: Discussionmentioning
confidence: 98%
“…Literature concerning the role of oxidative stress in mechanotransduction and adaptive responses in endothelial cells is more abundant and allows a better understanding of both the mechanical forces involved and the cellular response ( Hsieh et al, 2014 ; Chatterjee, 2018 ; Roux et al, 2020 ; Psefteli et al, 2021 ). Some studies in cartilage also contribute to the characterization of mechanical loading and redox state alterations ( Coleman et al, 2017 ; Walsh et al, 2019 ), with evidence supporting that inflammation induced by mechanical loading is ROS-mediated ( Kamalathevan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This negatively-charged hair/gel-like surface layer comprises glycoproteins (syndecan, glycipan, CD44) with glucosaminoglycan side-chains (heparan sulfate, chrondroitin sulfate), long-chain hyaluronic acid and glycolipids; it regulates fluid homeostasis, albumin transcytosis (218) and permeability (455), and minimises adhesion and emigration of blood cells. Glycocalyx sialic acid residues regulate EC redox state via modulation of shear stress-induced Nrf2-mediated signaling (331). This is of relevance considering that sialic acids are emerging as important players in the pathophysiology of SARS-CoV-2 (330), their incorporation into cell membranes is influenced by the diet (see nutrition section) and linked to complex immune responses (318).…”
Section: The Endothelium As a Nexus Of Whole-body Redox Regulationmentioning
confidence: 99%